Work-related stress and sleep problems among small-scale miners in Ghana: The role of psychological factors - Emmanuel Nyaaba; Vanessa Francesca Epis; Lawrence Guodaar; Razak M. Gyasi (PLoS ONE, 2025)
Objectives Sleep problems (SP) are prevalent among small-scale miners, yet little is known about their psychological and occupational determinants. We examined the association between work-related stress (WRS) and SP among small-scale miners in Ghana and explored the mediating roles of anxiety and depression in this association., Methods In this community-based cross-sectional study, data were collected from 664 miners in Obuasi,Ghana. WRS and SP were assessed using the Perceived Stress Scale (PSS-4) and the WHO Disability Assessment Schedule 2.0 (WHODAS 2.0), respectively, while anxiety and depression were measured using the GAD-7 and PHQ-9. Adjusted multivariate regressions and bootstrapped serial mediation models (Hayes’ PROCESS Model 6) evaluated the hypothesized pathways. Results The mean (SD) age was 28.8 (8.2) years, and 84.3% were males. WRS was significantly associated with SP (B = 0.2964, 95% CI = 0.2398–0.3530), with both direct (42.5%) and indirect (57.5%) effects. Anxiety mediated 38.0% of the total effect, depression 11.4%, and the anxiety–depression pathway 8.1%. Conclusions The study findings suggest that anxiety and depression serially mediate the WRS–SP link. These results underscore the need to address occupational stressors and incorporate mental health support into workplace policies to improve sleep quality and overall well-being in this vulnerable workforce.